Prior COVID-19 infection may increase risk for developing endothelial dysfunction following hematopoietic cell transplantation - Ariagno, Sydney; Ragoonanan, Dristhi; Khazal, Sajad; Mahadeo, Kris M.; Cisneros, Gabriel Salinas; Zinter, Matt S.; Blacken, Robyn A.; Mohan, Gopi; Lehmann, Leslie E.; Ferdjallah, Asmaa; Mara, Kristin C.; Kohorst, Mira A. (Frontiers in Oncology, 2023)
Endothelial dysfunction underlies many of the major complications following hematopoietic cell transplantation (HCT), including transplant-associated thrombotic microangiopathy (TA-TMA), veno-occlusive disease/ sinusoidal obstruction syndrome (VOD/SOS), and engraftment syndrome (ES). Emerging evidence similarly implicates endothelitis and microangiopathy in severe COVID-19-related multi-system organ dysfunction. Given the overlap in these two illness states, we hypothesize that prior COVID-19 infection may increase risk for HCT-related endotheliopathies. This retrospective, multicenter study included patients aged 0-25 years who underwent autologous or allogeneic HCT for any indication between January 1, 2020 and September 21, 2021, with close attention to those infected with COVID-19 in either the six months prior to transplant or twelve months following transplant. Incidences of TA-TMA, VOD/SOS, and ES were compared among patients with COVID-19 infection pre-HCT and post-HCT, as well as with historical controls who were never infected with SARS-CoV-2. Those who underwent HCT following COVID-19 infection displayed significantly increased rates of TA-TMA compared to those who were never infected. Additionally, our data suggests a similar trend for increased VOD/SOS and ES rates, although this did not reach statistical significance. Therefore, a history of COVID-19 infection prior to undergoing HCT may be a nonmodifiable risk factor for endothelial-related complications following HCT. Further studies are warranted to better clarify this relationship among larger cohorts and in the era of the Omicron SARS-CoV-2 variants.